Emulsions comprising acrylic polymer particles and related methods
By using an aqueous emulsion containing specific acrylic polymer particles, the problems of long bonding time of existing water-based adhesives and poor bonding effect under high temperature and high humidity are solved, and the effect of rapid development of bonding characteristics and maintaining bonding under harsh conditions is achieved.
Patent Information
- Application Number
- CN202280100270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing water-based adhesives take a long time to form bonds and are easily contaminated by moisture under high temperature or high humidity conditions, resulting in poor bonding effect.
An emulsion is provided that contains water, an emulsifier and acrylic polymer particles dispersed in water, including specific monomer units and chain end groups, capable of exhibiting adhesive properties within one minute of spraying.
The emulsion is capable of maintaining clamping bonding in the foam block within one minute of spraying and maintaining bonding effect when exposed to high temperature and/or high humidity aging.
Smart Images

Figure BDA0005320671800000051 
Figure BDA0005320671800000281 
Figure BDA0005320671800000321
Abstract
Description
Background Technology
[0001] Pressure-sensitive adhesives (often referred to as PSAs) can be used for a variety of purposes. Applying a PSA may involve applying an adhesive polymer composition in an organic solvent or as an emulsion to a substrate and subsequently removing the solvent or water. Water-based adhesives offer desirable advantages over their traditional solvent-based counterparts because they can have low or no volatile organic compounds and can be non-flammable.
[0002] CN107573453 (published September 19, 2017) discloses a water-based, one-component, water-based spray adhesive. WO2020 / 245690 (published May 21, 2020) and CN113308903 (published May 26, 2021) disclose water-based acrylic adhesive compositions. EP2246403 (published April 16, 2010) discloses a water-based floor or contact adhesive. JP2008184494 and JP2008184495 (published January 9, 2007) disclose aqueous dispersions of particulate polymers and related adhesives. U.S. Patent Application Publication No. 2022 / 0033692 (Muller et al.) discloses polymer latex compositions and one-component water-based contact adhesives comprising such polymer latex compositions. U.S. Patent No. 5,553,455 (Shah) discloses an aqueous contact adhesive comprising an aqueous emulsion of an emulsified acrylic polymer and an elastomeric latex, particularly natural rubber latex. U.S. Patent No. 5,300,554 (Krell et al.) discloses an aqueous contact adhesive dispersion comprising a copolymer of a vinyl ester of an aliphatic carboxylic acid having 2-12 carbon atoms and an acrylate of an aliphatic alcohol having 4-12 carbon atoms. U.S. Patent No. 10,221,343 (Qie et al.) discloses a one-component, fast-curing aqueous adhesive emulsion comprising a core-shell acrylic polymer. U.S. Patent No. 11,021,629 (Iyer et al.) discloses a two-part aqueous coating composition, wherein a first coating component may comprise one or more polymers, and a second coating component may comprise a flocculant. Summary of the Invention
[0003] This disclosure provides an emulsion comprising acrylic polymer particles in water. Typically and advantageously, the emulsion exhibits adhesive properties rapidly, for example, within one minute of being sprayed onto a substrate.
[0004] In one aspect, this disclosure provides an emulsion comprising water, an emulsifier, and acrylic polymer particles dispersed in the water. The acrylic polymer particles comprise monomer units of alkyl acrylates, alkyl methacrylates, or combinations thereof, wherein the alkyl group has at least eight carbon atoms; at least 1% by weight of acid-functionalized monomer units based on the total weight of the acrylic polymer particles; and high TT. g The monomeric unit includes at least one of tert-octylacrylamide, tert-butyl methacrylate, tert-butyl acrylate, isobornyl acrylate, or isobornyl methacrylate; and a chain-end group having at least four carbon atoms and a thioether group. In some embodiments, the emulsion provides an adhesive capable of maintaining a clamped bond within the foam block for one minute after the emulsion is applied.
[0005] In another aspect, this disclosure provides a method for preparing the above-described emulsion. The method comprises combining components including: water; an emulsifier; alkyl acrylates, alkyl methacrylates, or combinations thereof; at least 1% by weight of an acid-functionalized monomer based on the total weight of the monomers; and a high-T... g Monomers; chain transfer agents containing thiol groups; and polymerization initiators, and alkyl acrylates, alkyl methacrylates, or combinations thereof; acid-functionalized monomers; high-T g Monomers, chain transfer agents, and optional emulsifiers are reacted to provide an emulsion.
[0006] In another aspect, this disclosure provides a method for preparing an adhesive article comprising a first substrate or a second substrate. The method includes: spraying the emulsion to provide an adhesive onto at least one of the first substrate or the second substrate; and adhering the first substrate and the second substrate together. In some embodiments, the first substrate and the second substrate are adhered within one minute after spraying.
[0007] In this application, terms such as “an,” “a,” and “the / described” are not intended to refer to a single entity, but rather to include a general category of specific examples that can be used for illustration. The terms “an,” “a,” “the,” and “described” are used interchangeably with the term “at least one (kind).” The phrases “at least one (kind) of…” and “containing at least one (kind) of…” followed by a list refer to any item in the list and any combination of two or more items in the list. Unless otherwise indicated, all numerical ranges include their endpoints and non-integer values between the endpoints (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.8, 4, and 5, etc.).
[0008] The terms “first” and “second” are used in this disclosure only in their relative sense. It should be understood that, unless otherwise specified, these terms are used for convenience in describing one or more embodiments only.
[0009] As used herein, the terms “acrylic acid” or “acrylate” include compounds having at least one of an acrylic acid group or a methacrylic acid group.
[0010] The term "(meth)acrylic acid" in relation to monomers, oligomers, or polymers refers to vinyl functionalized alkyl esters formed as products of the reaction of alcohols with acrylic acid or methacrylic acid.
[0011] The term "polymer" or "of polymers" includes homopolymers and copolymers, as well as homopolymers or copolymers that can be formed in miscible blends, for example, by co-extrusion or by reactions including, for example, transesterification. The term "copolymer" includes random copolymers, block copolymers, graft copolymers, and star copolymers.
[0012] The term "crosslinking" refers to linking polymers together through covalent chemical bonds (usually via crosslinking molecules or groups) to form a network polymer. Crosslinked polymers are generally characterized by insolubility, but can be swollen in the presence of suitable solvents.
[0013] The term "alkyl group" and the prefix "alkane-" encompass straight-chain, branched, and cyclic groups. In some embodiments, unless otherwise specified, the alkyl group has up to 30 carbons (in some embodiments, up to 25, 20, 18, 16, or 15 carbons). The cyclic group can be monocyclic or polycyclic. The alkyl group is neither fluorinated nor perfluorinated.
[0014] Those skilled in the art are well aware that PSA possesses properties including (1) strong and persistent adhesion, (2) adhesion with pressure not exceeding finger pressure, (3) sufficient ability to remain on the adherend, and generally, (4) sufficient cohesive strength to be cleanly removed from the adherend. PSA is viscous and has the ability to adhere without being activated by any energy source, such as light, heat, or chemical reaction. Materials found well for use as PSA are polymers designed and formulated to exhibit the desired viscoelasticity, thereby achieving a desired balance of adhesive force, peel adhesion, and shear retention. One method that can be used to identify pressure-sensitive adhesives is the Dahlquist criterion. As described in "Handbook of Pressure Sensitive Adhesive Technology," edited by Donatas Satas, 2nd edition, page 172, Van Nostrand Reinhold, New York (NY), 1989, this guideline defines pressure-sensitive adhesives as having a pressure sensitivity greater than 3 × 10⁻⁶. -6 cm 2 / Dyne's creep compliance adhesive. Alternatively, since the modulus is approximately the reciprocal of the creep compliance, pressure-sensitive adhesives can be defined as having a storage modulus of less than approximately 3 × 10⁻⁶. 5 N / m 2 Adhesive.
[0015] The foregoing overview of this disclosure is not intended to describe every disclosed embodiment or implementation of this disclosure. The following description illustrates exemplary embodiments in more detail. Therefore, it should be understood that the accompanying drawings and the following description are for illustrative purposes only and should not be construed as undue limitation on the scope of this disclosure. Attached Figure Description
[0016] A more complete understanding of this disclosure can be achieved by referring to the accompanying drawings and the following detailed description of various embodiments thereof, wherein:
[0017] Figure 1a is a perspective view of the foam blocks after spraying with the emulsion of this disclosure and before clamping and bonding.
[0018] Figures 1b and 1c are perspective views showing the formation of a clamping bond within the foam cube of Figure 1a after emulsion spraying using the present disclosure; and
[0019] Figure 1d is a perspective view of the foam blocks in Figures 1a, 1b and 1c after they have been clamped and bonded. Detailed Implementation
[0020] One of the disadvantages of using water-based adhesives in sprayable applications is that water has a significantly longer evaporation time compared to the common organic solvents used in solvent-based adhesives. Therefore, water-based adhesives require a long time to develop PSA properties and sufficient tack to bond the substrates together (e.g., up to 30 minutes or longer in some cases), while organic solvent-based spray adhesives may achieve bonding in just seconds or minutes. Water-based spray adhesives can also be susceptible to moisture contamination and may not hold up well under high temperature or high humidity conditions.
[0021] The water-based adhesives provided by the emulsions and methods described here are competitive with solvent-based adhesives in terms of the time required for bond formation. In some embodiments, the emulsion provides an adhesive capable of maintaining a tight bond within the foam block within one minute of spraying the emulsion. In some embodiments, the bonding effect provided by the emulsion is maintained even after aging with exposure to high temperatures and / or high humidity.
[0022] Acrylic polymer particles that can be used in the emulsions and methods of this disclosure comprise monomer units of at least one alkyl acrylate, alkyl methacrylate, or combinations thereof, wherein the alkyl group has at least eight carbon atoms. Examples of suitable alkyl (meth)acrylates include those represented by formula I:
[0023] CH2=C(R')COOR(I)
[0024] Wherein R' is hydrogen or methyl, and R is an alkyl group having 8 to 30, 8 to 20, 8 to 18, 8 to 16, or 8 to 12 carbon atoms, and may be straight-chain or branched. Examples of suitable monomers represented by Formula I include 2-ethylhexyl acrylate, n-octyl acrylate, 2-octyl acrylate, isooctyl acrylate, n-nonyl acrylate, n-decyl acrylate, isodecyl acrylate, n-dodecyl acrylate, isotetradecyl acrylate, n-tridecyl acrylate, n-tetradecyl acrylate, octadecyl acrylate, isooctadecyl acrylate, dodecyl acrylate, and methacrylates of the above acrylates. Suitable monomer units also include mixtures of at least two or at least three structural isomers of secondary alkyl (meth)acrylates of Formula II:
[0025]
[0026] Where R 1 and R 2 Each independently is C1 to C 30 Saturated linear alkyl groups; R 1 and R 2 The total number of carbons in it ranges from 7 to 31, and R 3 It is H or CH3. In some implementations, R 1 and R 2 The total number of carbons in the monomers can be 7 to 27, 7 to 25, 7 to 21, 7 to 17, 7 to 11, 7, 11 to 27, 11 to 25, 11 to 21, 11 to 17, or 11. Methods for manufacturing and using such monomers and monomer mixtures are described in U.S. Patent No. 9,102,774 (Clapper et al.). Mixtures of one or more monomers of Formula I, Formula II, or combinations of Formulas I and II can be used in acrylic polymer particles. In some embodiments, acrylates, methacrylates, or combinations thereof comprise at least one acrylate (as opposed to methacrylates).
[0027] In some embodiments, the acrylic polymer particles used in practicing this disclosure comprise up to 90% by weight of at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combinations thereof, wherein the alkyl group has at least eight carbon atoms, as described above in any of its embodiments. In some embodiments, the acrylic polymer particles used in practicing this disclosure comprise at least 40% by weight of at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combinations thereof, wherein the alkyl group has at least eight carbon atoms, as described above in any of its embodiments. The weight percentage values are based on the total weight of the monomer units in the acrylic polymer particles. In some embodiments, the acrylic polymer particles comprise 40% to 90% by weight, 40% to 75% by weight, 40% to 60% by weight, 45% to 55% by weight, 60% to 90% by weight, 65% to 85% by weight, or 70% to 80% by weight of at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combinations thereof, wherein the alkyl group has at least eight carbon atoms, as described above in any of its embodiments. In methods for preparing emulsions, these weight percentages refer to the amount of alkyl acrylates, alkyl methacrylates, or combinations thereof, wherein the alkyl group has at least 8 carbon atoms, based on the total weight of the monomers in the combined components.
[0028] In some embodiments, the acrylic polymer further comprises monomer units of at least one of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, and in some embodiments, comprises C1-C6 alkyl acrylates. Suitable C1-C6 (meth)alkyl acrylates include methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, hexyl acrylate, cyclohexyl acrylate, and combinations thereof. In some embodiments, the C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates are linear or branched. In some embodiments, the second monomer is methyl acrylate or n-butyl acrylate. In some embodiments, the acrylic polymer particles used to practice this disclosure comprise up to 25% by weight of monomer units of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, as described above in any of its embodiments. In some embodiments, the acrylic polymer particles used to practice this disclosure comprise at least 5% by weight of monomer units of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, as described above in any of its embodiments. The weight percent (%) values are based on the total weight of the monomer units in the acrylic polymer particles. In some embodiments, the acrylic polymer particles comprise 5 to 25 wt%, 5 to 15 wt%, 10 to 25 wt%, or 15 to 25 wt% monomer units of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, as described above in any of its embodiments. In methods of preparing emulsions, these weight percent values refer to the amount of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates based on the total weight of the monomers in the combined components.
[0029] The monomer units comprising at least 1% by weight of the acrylic polymer particles used in the emulsions and methods of this disclosure include acid functional groups. In some embodiments, the acid functional monomers include carboxylic acids. Monomers having a carboxylic acid group include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, ethylacrylic acid, crotonic acid, citrate, cinnamic acid, ethyl β-carboxyacrylate, and 2-methacryloyloxyethyl succinate. Sulfonic and phosphonic acid functional monomers such as 2-acrylamido-2-methylpropanesulfonic acid and vinylphosphonic acid may also be useful. Monomer units including acid functional groups include salts of these acids, such as alkali metal salts and ammonium salts. In some embodiments, the acid functional monomer units include acrylic acid monomer units, methacrylic acid monomer units, or a combination of acrylic acid monomer units and methacrylic acid monomer units. In some embodiments, based on the total weight of the monomer units in the acrylic polymer particles, the acrylic polymer particles contain up to 5% by weight or up to 4% by weight of acid functional monomer units. In some embodiments, the acrylic polymer particles comprise 1 wt% to 5 wt%, 1.5 wt% to 5 wt%, 2 wt% to 5 wt%, 2 wt% to 4 wt%, or 2 wt% to 3.8 wt% of acid-functionalized monomer units. In methods of preparing the emulsion, these weight percentages refer to the amount of acid-functionalized monomers, based on the total weight of monomers in the combined components.
[0030] The acrylic polymer particles that can be used in the emulsions and methods of this disclosure also contain "high T" g "The monomer unit of the monomer, which provides the glass transition temperature (T) during homopolymerization." g The monomer is a homopolymer with a temperature range of at least 40°C or at least 50°C (i.e., the homopolymer formed from the monomer has a temperature range of at least 40°C or at least 50°C). g T of homopolymer g Measurements were taken using differential scanning calorimetry, and many are reported in the "Polymer Properties Database" found at polymerdatabase.com. High T g The monomer has a single (meth)acryloyl group and comprises at least one of tert-butyl methacrylate, tert-butyl acrylate, isobornyl methacrylate, isobornyl acrylate, tert-octylacrylamide, or tert-octylmethacrylamide. Isobornyl acrylate and isobornyl methacrylate are provided with T values of 97°C and 110°C, respectively. g The homopolymer, similar to the T-polymer of tert-butyl methacrylate at 118°C. g Therefore, the examples prepared from isobornyl acrylate and isobornyl methacrylate are considered to behave similarly to the examples prepared from tert-butyl methacrylate described below. In some embodiments, high T g The monomer comprises at least one of tert-octylacrylamide, tert-butyl methacrylate, or tert-butyl acrylate. In some embodiments, high T gThe monomer comprises at least one of tert-octylacrylamide or tert-butyl methacrylate. In some embodiments, high T g The monomer is tert-octylacrylamide. In some embodiments, high T g The monomer is tert-butyl methacrylate. Other high-T monomers can be avoided in the acrylic polymer particles disclosed herein. g Monomers such as methyl methacrylate, styrene, and vinyl acetate.
[0031] In some embodiments, based on the total weight of the monomer units in the acrylic polymer particles, the acrylic polymer particles used in practicing this disclosure contain 3% to 35% by weight of high T g Monomer units, as described above in any of its embodiments. In some embodiments, the acrylic polymer particles used in practicing this disclosure may contain 3% to 15% by weight, 5% to 10% by weight, 20% to 35% by weight, or 20% to 30% by weight of high T. g The monomer unit is as described above in any of its embodiments. In some embodiments, the acrylic polymer particles contain no more than 1, 0.5, 0.1, 0.05, or 0 monomer units of at least one of methyl methacrylate, styrene, or vinyl acetate. In methods of preparing emulsions, these weight percentages refer to high T g The amount of monomers is based on the total weight of the monomers in the composite components.
[0032] Acrylic polymer particles that can be used in the emulsions and methods of this disclosure comprise chain end groups having at least four carbon atoms and connected to the acrylic polymer via a thioether group. The thioether group is represented by the formula -R2C-S-CR2-, where R is hydrogen or an alkyl group. In some embodiments, the acrylic polymer particles are free of thiocarbonyl-thio groups (i.e., -C(S)-S-). In some embodiments, the chain end groups have at least 6 or 8 carbon atoms. In some embodiments, the chain end groups have up to 30, 24, 20, 18, 16, or 12 carbon atoms. The end groups having at least four carbon atoms and connected to the polymer via a thioether group are typically introduced into the acrylic polymer particles during emulsion polymerization using a thiol chain transfer agent, as described in further detail below. Examples of useful chain transfer agents having thiol groups include alkyl thiols and mercaptocarboxylic acid esters having 4-18 carbon atoms. Specific examples of useful chain transfer agents include isooctyl mercaptoacetate, dodecyl mercaptoacetate, isooctyl 3-mercaptopropionate, ethylhexyl mercaptoacetate, butyl 3-mercaptopropionate, butyl mercaptoacetate, octyl thiol, 1-dodecanethiol, tert-dodecyl thiol, hexadecyl thiol, octadecyl thiol, trimethylolpropane-tri-(3-mercaptopropionate), pentaerythritol-tetra-(3-mercaptoacetate), pentaerythritol-tetra-(thiolactic acid ester), and dipentaerythritol-hexa-(mercaptoacetate). In some embodiments, based on the total weight of the acrylic polymer particles, the acrylic polymer particles used in practicing this disclosure may contain 0.005% to 0.1% by weight of chain end groups having at least four carbon atoms and connected to the polymer via thioether groups. In some embodiments, based on the total weight of monomer units in the acrylic polymer particles, the acrylic polymer particles used in practicing this disclosure may contain 0.01 wt% to 0.1 wt%, 0.02 wt% to 0.075 wt%, 0.025 wt% to 0.06 wt%, or 0.03 wt% to 0.04 wt% of chain end groups. In methods of preparing emulsions, these weight percentages refer to the amount of chain transfer agent, based on the total weight of monomers in the combined components.
[0033] In some embodiments, the acrylic polymer particles are crosslinked. Crosslinked acrylic polymer particles can be manufactured, for example, by incorporating one or more multifunctional crosslinking monomers into the formulation. In some embodiments, the acrylic polymer particles that can be used in the emulsions and methods of this disclosure also comprise monomer units of multifunctional acrylates or multifunctional methacrylates. Suitable multifunctional monomers include diacrylates of diols, such as ethylene glycol diacrylate, diethylene glycol diacrylate, propylene glycol diacrylate, butane-1,3-dimethyl diacrylate, pentane glycol diacrylate, hexanediol diacrylate (including 1,6-hexanediol diacrylate), heptanediol diacrylate, octanediol diacrylate, nonanediol diacrylate, decanedanediol diacrylate, and dimethacrylates of any of the aforementioned diacrylates. Other suitable multifunctional monomers include polyacrylates of polyols, such as glyceryl triacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, neopentyl glycol diacrylate, dipentaerythritol pentaacrylate, methacrylates of the aforementioned acrylates, and combinations thereof. Other suitable multifunctional crosslinking monomers include divinylbenzene, allyl methacrylate, diallyl maleate, diallyl phthalate, and combinations thereof. Further suitable multifunctional crosslinking monomers include multifunctional acrylate oligomers comprising two or more acrylate groups. Multifunctional acrylate oligomers may be urethane acrylate oligomers, epoxy acrylate oligomers, polyester acrylates, polyether acrylates, polyacrylate acrylates, methacrylates of any of the aforementioned acrylates, or combinations thereof. Any combination of these crosslinking monomers may be available. In some embodiments, the acrylic polymer used in the compositions and methods of this disclosure may contain monomer units derived from crosslinking monomers in amounts not exceeding 1 wt%, 0.5 wt%, 0.25 wt%, 0.1 wt%, 0.05 wt%, or 0.01 wt%. The acrylic polymer particles may be free of crosslinking monomer units. In some embodiments, based on the total weight of monomer units in the acrylic polymer particles, the acrylic polymer particles used in practicing this disclosure may contain 0 wt% to 0.1 wt% of crosslinking monomer units. In some embodiments, the acrylic polymer particles used in practicing this disclosure may contain 0.001 wt% to 0.1 wt%, 0.005 wt% to 0.05 wt%, or 0.0075 wt% to 0.025 wt% of crosslinking monomer units. In methods of preparing emulsions, these weight percentages refer to the amount of crosslinking monomers, based on the total weight of monomers in the combined components.
[0034] In some embodiments, the acrylic polymer particles that can be used in the emulsions and methods of this disclosure further comprise monomer units having at least one ketone or aldehyde functional group. Examples of ketone-containing monomers include diacetone acrylamide, acetoacetoxyethyl (meth)acrylate, acetoacetoxybutyl (meth)acrylate, acetoacetoxyethyl (meth)acrylamide, acetoacetamoxyethyl (meth)acrylate, vinyl methyl ketone, and allyl acetoacetate. Aldehyde-containing monomers such as acrolein can also be used in the acrylic polymer particles. In some embodiments, at least 1 wt%, 0.95 wt%, 0.75 wt%, 0.5 wt%, 0.25 wt%, 0.1 wt%, 0.05 wt%, or 0.01 wt% of the monomer units in the acrylic polymer particles that can be used in the emulsions and methods of this disclosure comprise at least one ketone or aldehyde functional group. In some embodiments, the acrylic polymer particles used in the emulsions and methods of this disclosure contain monomer units comprising at least 4 wt%, 3 wt%, 2.5 wt%, 2.0 wt%, 1.75 wt%, 1.5 wt%, or 1.35 wt% of a monomer unit having at least one ketone or aldehyde functional group. The acrylic polymer particles may not contain monomer units having at least one ketone or aldehyde functional group. In some embodiments, based on the total weight of monomer units in the acrylic polymer particles, the acrylic polymer particles used in practicing this disclosure may contain 0.1 wt% to 5 wt% of monomer units having at least one ketone functional group. In some embodiments, the acrylic polymer particles used in practicing this disclosure may contain 0.2 wt% to 4 wt% or 0.5 wt% to 2 wt% of monomer units having at least one ketone functional group. In methods for preparing emulsions, these weight percentages refer to the amount of monomers having at least one ketone or aldehyde functional group, based on the total weight of monomers in the combined components.
[0035] In some embodiments where the acrylic polymer particles used in practicing this disclosure further comprise monomer units having at least one ketone functional group, the emulsions of this disclosure also comprise a polyhydrazide, polyhydrazide, or polyamine (in some embodiments, a polyhydrazide) crosslinking agent. Examples of suitable polyhydrazide crosslinking agents include adipate dihydrazide, oxalate dihydrazide, ethylmalonate dihydrazide, succinate dihydrazide, glutarate dihydrazide, tartrate dihydrazide, pimecrolate dihydrazide, 9,10-dihydro-9,10-ethyleneanthracene-11,12-dicarboxylic acid dihydrazide, valine dihydrazide, phthalate dihydrazide, isophthalate dihydrazide, terephthalate dihydrazide, sebacic acid dihydrazide, malonate dihydrazide, maleate dihydrazide, fumarate dihydrazide, and itaconic acid dihydrazide. Examples of suitable polyhydrazide crosslinking agents include dihydrazide-based compounds of dihydrazine ketones and aromatic hydrocarbons (e.g., 1,4-dihydrazidebenzene and 2,3-dihydrazidenaphthalene). Examples of suitable polyamine crosslinking agents include ethylenediamine, propylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, diethylenetriamine, and triethylenetetramine. The polyhydrazide, polyhydrazide, or polyamine crosslinking agent may be added to the emulsion before or after the emulsion polymerization reaction described below. In some embodiments, the polyhydrazide or polyhydrazide crosslinking agent is added to the emulsion after polymerization to form acrylic polymer particles. In some embodiments, the crosslinking agent is a polyhydrazide. The emulsion may contain unreacted polyhydrazide crosslinking agent, or the emulsion may include a ketone-polyhydrazide reaction product that may contain polyhydrazone bonds. In some embodiments, the amount of polyhydrazide, polyhydrazide, or polyamine (in some embodiments, polyhydrazide) crosslinking agent in the emulsion is such that for every amount of ketone or aldehyde functional group in the acrylic polymer particles, there are 0.5 to 1.5 equivalents of functional groups from the crosslinking agent. In some embodiments, based on the total weight of the emulsion, the emulsion contains up to 1 wt%, 0.5 wt%, 0.25 wt%, or 0.2 wt%, and / or at least 0.005 wt%, 0.01 wt%, 0.05 wt%, or 0.1 wt%, of polyhydrazide, polyhydrazide, or polyamine (in some embodiments, polyhydrazide) crosslinking agent.
[0036] Crosslinked acrylic polymer particles can be crosslinked within the particles, such as by introducing multifunctional crosslinking monomer units as described above between the particles, such as by using polyhydrazide, polyhydrazine, or polyamine (in some embodiments, polyhydrazine) crosslinking agents to crosslink monomer units including at least one of ketone or aldehyde functional groups, or crosslinking within and between particles. Intraparticle crosslinking can also occur when the multifunctional crosslinking monomer is not included in the component to be polymerized. For example, some monomers such as acetyl acetoxyethyl methacrylate monomer may include some diacrylate impurities that can crosslink acrylic polymer particles. The combination of tert-octylacrylamide and acid-functional monomers can lead to acid-base interactions in the acrylic polymer particles, which can effectively induce intraparticle crosslinking. Intraparticle or interparticle crosslinking can be demonstrated by the gel content of the emulsion. In some embodiments, the emulsion has a gel content of at least 28%. In some embodiments, when the emulsion contains a polyhydrazine, polyhydrazine, or polyamine (in some embodiments, polyhydrazine) crosslinking agent, the emulsion has a gel content of at least 60%, 70%, 80%, or 90%. In some embodiments, if the acrylic polymer particles are crosslinked only within the particles, the emulsion has a gel content of less than 60%, 50%, 40%, or 30%. The gel content is determined by the methods provided in the following examples.
[0037] In some embodiments, the acrylic polymer particles used in practicing this disclosure comprise at least 40% to 90% by weight of a monomer unit of at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, wherein the alkyl group has at least 8 carbon atoms; 0% to 25% by weight of C1-C6 alkyl acrylate; 2% to 5% by weight of an acid-functionalized monomer unit; 3% to 15% by weight of tert-octylacrylamide; 0% to 5% by weight of a monomer unit having at least one ketone or aldehyde functional group, and 0.02% to 0.075% by weight of chain-end groups, based on the total weight of the monomer units in the acrylic polymer particles. In some of these embodiments, the acrylic polymer particles comprise 1.6% to 2.5% by weight of an emulsifier, based on the total weight of the monomer units in the acrylic polymer particles. In some embodiments, the acrylic polymer particles comprise at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combination thereof, ranging from 40% to 90% by weight, wherein the alkyl group has at least 8 carbon atoms; C1-C6 alkyl acrylate ranging from 0% to 25% by weight; acid-functional monomer unit ranging from 2% to 5% by weight; tert-butyl methacrylate ranging from 10% to 30% by weight; monomer unit having at least one ketone or aldehyde functional group ranging from 0% to 5% by weight, based on the total weight of the monomer units in the acrylic polymer particles; and chain end groups ranging from 0.02% to 0.075% by weight.
[0038] In some embodiments, based on the total weight of monomer units in the acrylic polymer particles, at least one monomer unit of alkyl acrylate, alkyl methacrylate, or combinations thereof (wherein the alkyl group has at least eight carbon atoms), acid-functionalized monomer unit, high-T g The monomer unit comprises at least 95%, 96%, 97%, 98%, 99%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, or 100% of the monomer unit, including the monomer unit of at least one of the monomer units of C1-C6 alkyl acrylate or C1-C6 alkyl methacrylate, the monomer unit of at least one of the monomer units of at least one of the monomer units as described above in any of its embodiments. Based on the total weight of the monomer units in the acrylic polymer particles, the acrylic polymer particles may contain less than 0.1%, 0.5%, or 1% of at least one of the following: N-hydroxymethylacrylamide, styrene, methyl methacrylate, vinyl ester, vinyl acetate, quaternary amino-functional (meth)acrylate, epoxy-functional (meth)acrylate, or silane-functional (meth)acrylate.
[0039] In some embodiments, the acrylic polymer particles in the emulsions of this disclosure and / or manufactured by the methods of this disclosure are not core-shell polymers with different monomer compositions in the core and shell. When referring to core-shell polymers, the core typically constitutes about 25% by weight of the core-shell polymer and may account for up to 83% by weight of the core-shell polymer. In this way, core-shell polymers differ from polymer particles prepared by seed polymerization, where the seed composition typically provides up to 10% by weight or up to 5% by weight of the polymer particles. Although polymerization results in a distribution of composition and molecular weight, in some embodiments, emulsion polymerization is not performed, such that the monomer composition is changed during polymerization to provide polymer particles with a core having a different glass transition temperature or different reactivity than the shell. In some embodiments, the acrylic polymer particles comprise monomer units of at least one alkyl acrylate, alkyl methacrylate, or combinations thereof (wherein the alkyl group has at least eight carbon atoms), acid-functionalized monomer units, high-T g The monomer unit, the optional monomer unit of at least one of C1-C6 alkyl acrylate or C1-C6 alkyl methacrylate, the optional monomer unit having at least one ketone or aldehyde functional group, and the optional polyfunctional crosslinking monomer.
[0040] In some embodiments, acrylic polymer particles constitute at least 70 wt%, 80 wt%, 95 wt%, or 99 wt% of the polymer in the emulsion. In some embodiments, the emulsion contains no more than 30 wt%, 20 wt%, 10 wt%, 5 wt%, or 1 wt% of a polymer, such as polychloroprene, natural rubber, synthetic polyisoprene, or polyvinyl alcohol. Depending on the amount of any additives described below, in some embodiments, based on the total amount of solids in the composition (i.e., excluding water), the emulsion may contain at least 70 wt%, 75 wt%, 80 wt%, 90 wt%, 95 wt%, 98 wt%, or 99 wt% of the acrylic polymer particles described above in any of its embodiments.
[0041] Acrylic polymers that can be used in the emulsions and methods of this disclosure are conveniently prepared by emulsion polymerization. Acrylic monomers or combinations of monomers as described above in any of its embodiments are combined with water and an emulsifier or a combination of emulsifiers, and then one or more monomers are polymerized. One or more of the comonomers may be emulsified first in a stirred aqueous phase before initiation. Many parameters of the emulsion polymerization technique can be adjusted by those skilled in the art. For example, initiators can be added according to a variety of possible schemes, and monomers can be added continuously or in staggered increments. Additionally, polymerization can be initiated in the presence of a previously prepared seed.
[0042] The emulsifier is present in the emulsion of this disclosure and in the components combined in the method for preparing the adhesive composition of this disclosure. In some embodiments, the emulsifier is an anionic surfactant. Available anionic surfactants include those comprising at least one hydrophobic portion (such as an alkyl, alkylaryl, and / or alkenyl group of about 6 to about 12 carbon atoms) and at least one anionic group selected from carboxyl, sulfate, sulfonate, phosphate, polyoxyethylene sulfate, polyoxyethylene sulfonate, polyoxyethylene phosphate, and / or a salt of such anionic group (such as an alkali metal salt (e.g., sodium salt, potassium salt) and an ammonium salt). Any fatty acid soap (e.g., alkyl succinate), ethoxylated fatty acid and / or its alkali metal ammonium salt, dialkyl sulfosuccinate, and sulfated oil can be useful. Some useful anionic surfactants include sodium lauryl sulfate, sodium lauryl ether sulfate, sodium dodecylbenzene sulfonate, and sulfosuccinate. Representative commercially available examples of anionic surfactants include: sodium lauryl sulfate, available under the trade name "POLYSTEP B-3" from Stepan Chemical Co.; sodium lauryl ether sulfate, available under the trade name "POLYSTEP B-12" from Stepan Chemical Co.; and sodium dodecylbenzene sulfonate, available under the trade name "RHODACAL DS-10" from Rhodia, Incorporated. Combinations of any of these surfactants may be used.
[0043] In some embodiments, the emulsifier may be copolymerized with a monomer or a mixture of monomers and incorporated into the acrylic polymer. The copolymerizable emulsifier has at least one group or only one group capable of reacting with the monomer or mixture of monomers. Such reactive groups include olefinically unsaturated groups such as vinyl and acrylate groups. Examples of polymerizable emulsifiers include sodium styrene sulfonate (commercially available from Alfa Aesar and Tosoh), sodium vinyl sulfonate, sodium polystyrene sulfonate, polyoxyethylene alkylphenyl ether ammonium sulfate (available under the trade name "HITENOL BC" from Dai Ichi Kogyo Seiyaku, Kyoto, Japan), including polyoxyethylene-nonylpropylene phenyl ether ammonium sulfate, polyoxyethylene styrene phenyl ether ammonium sulfate (such as available under the trade name "HITENOL AR" from Dai Ichi Kogyo Seiyaku, Kyoto, Japan), and polyoxyethylene alkyl ether sulfate (such as available under the trade name "HITENOL KH" from Dai Ichi Kogyo Seiyaku, Kyoto, Japan).
[0044] Based on the weight of the acrylic polymer particles, the total amount of surfactant used to prepare the emulsion is typically 5 wt%, 3 wt%, 2 wt%, 1.75 wt%, 1.5 wt%, or 1.3 wt% or less. In some embodiments, the total amount of emulsifier used is anionic in nature.
[0045] In some implementations, a small amount (e.g., less than 5% by weight of the total surfactant amount) of nonionic surfactant may be used as needed. A variety of surfactants known to those skilled in the art can be used. Representative commercial examples of nonionic surfactants include TRITON CG 600 (polyalkyl glucoside) from Dow Chemical Company, polyoxyethylene alkyl ethers such as LUTENSOL from BASF, ethylene oxide-propylene oxide copolymers under the trade name MAKON from Stepan, and polymerizable surfactants comprising polyoxyethylene alkyl phenyl ethers such as NOIGEN RN from Montello.
[0046] Emulsion polymerization is carried out in water. Water is present in the emulsions of this disclosure. Based on the total weight of the emulsion, the amount of water in the emulsions of this disclosure and / or prepared by the methods of this disclosure is typically at least 25% by weight or 30% by weight. Based on the total weight of the emulsion, the amount of water in the emulsion can be up to 65% by weight, 60% by weight, 55% by weight, 50% by weight, 45% by weight, or 40% by weight. Based on the total weight of the emulsion, the usable amount of water in the emulsion can range from 25% by weight to 65% by weight, 35% by weight to 60% by weight, or 45% by weight to 55% by weight.
[0047] The product comprises at least one alkyl acrylate, alkyl methacrylate, or a combination thereof (wherein the alkyl group has at least eight carbon atoms), an acid-functionalized monomer, or a high-T gThe polymerization of monomers, optionally C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, optionally monomers having at least one ketone or aldehyde functional group, and optionally polyfunctional crosslinked monomers to form acrylic polymer particles as described above in any of its embodiments typically involves a polymerization initiator. Polymerization initiators suitable for preparing the acrylic polymer particles that can be used in this disclosure include initiators that generate free radicals when exposed to heat, which initiate the polymerization of monomers or mixtures of monomers. Water-soluble initiators can be used to prepare acrylic polymer particles via emulsion polymerization. Suitable water-soluble initiators include potassium persulfate, ammonium persulfate, sodium persulfate, and mixtures thereof. Redox initiators include the reaction products of the aforementioned persulfates and reducing agents, such as those selected from metabisulfites, formaldehyde hyposulfites, 4,4'-azobis(4-cyanopentanoic acid) and their soluble salts (e.g., sodium and potassium salts), and higher sulfinic acid derivatives such as those available under the trade names "BRUGGOLITE FF6 M" and "BRUGGOLITE TP1651" from L. Brüeggemann GMBH & Co. KG., Heilbronn, Germany. In use, the initiator may comprise: about 0.01 parts by weight to about 1 part by weight, 0.05 parts by weight to about 1 part by weight, or about 0.1 parts by weight to about 0.5 parts by weight, based on 100 parts by weight of monomer. A final redox initiator pair may be added at the end of the reaction to increase the conversion rate. In some embodiments of the method for preparing the adhesive according to this disclosure, the polymerization initiator is a water-soluble initiator (e.g., a water-soluble free radical initiator) or a combination of water-soluble initiators comprising an oxidant and a reducing agent.
[0048] Catalysts can help accelerate the generation of free radicals. Examples of suitable catalysts include ferrous sulfate and ethylenediaminetetraacetic acid (EDTA).
[0049] Emulsion polymerization can be carried out at a variety of temperatures. The temperature can be readily selected by those skilled in the art and can depend at least in part on the initiator used. In some embodiments, polymerization is carried out at temperatures in the range of 10°C to 100°C, 30°C to 90°C, 40°C to 80°C, or 65°C to 75°C. In some embodiments, polymerization is carried out at temperatures not exceeding 70°C, and in some embodiments, at temperatures in the range of 30°C to 70°C, 40°C to 70°C, or 65°C to 70°C.
[0050] In addition to the combinations of monomers, water, emulsifiers, initiators, chain transfer agents, and optional catalysts described above in any of its embodiments, the following additives may also be optionally included in the emulsion compositions that can be used in practicing this disclosure: inhibitors such as hydroquinone, pigments, dyes, rheology modifiers, thickeners, viscous agents, plasticizers, antioxidants (e.g., hindered phenols, amines, and sulfur and phosphorus hydroperoxide decomposers), stabilizers (e.g., UV absorbers, hindered amine light stabilizers, and heat stabilizers), fillers (e.g., inorganic fillers such as talc, zinc oxide, titanium dioxide, and alumina), preservatives, biocides, corrosion inhibitors, flame retardants, and defoamers. These additives, if used, will be present at concentrations known to those skilled in the art, provided that they do not unacceptably affect the advantages provided by this disclosure.
[0051] The acrylic polymer particles that can be used in the emulsions and methods of this disclosure have sizes in the range of 50 nm to 10 μm, 50 nm to 5 μm, 50 nm to 200 nm, 50 nm to 125 nm, 50 nm to 100 nm, or 200 nm to 500 nm, as measured by dynamic light scattering, a technique well known to those skilled in the art of emulsion polymerization. In some embodiments, the particle size is 500 nm or smaller, 400 nm or smaller, 300 nm or smaller, 200 nm or smaller, 125 nm or smaller, or 100 nm or smaller. In some embodiments, the particle size is at least 50 nm, at least 100 nm, or at least 130 nm. In some embodiments, particle sizes of 125 nm, 100 nm, or smaller can be achieved by preparing seeds using a relatively large amount of emulsifier (e.g., greater than 5 wt% or at most or at least 10 wt% based on the total weight of the acrylic polymer particles), followed by polymerizing the remaining monomers using the aforementioned amount of surfactant.
[0052] After emulsion polymerization, the emulsions of this disclosure and / or prepared by the methods of this disclosure are generally acidic, as determined using a standard pH meter or pH test paper known to those skilled in the art. In some embodiments, the pH of the emulsion is about 3, about 4, or in the range of 3 to 4. In some embodiments of the emulsions and methods of this disclosure, the emulsion also contains a base, for example, to raise the pH. In some embodiments, the pH is raised to at least 3.5, 4, 5, or 6. In some embodiments, the pH does not exceed 7. Examples of suitable bases include ammonia (e.g., ammonia water or ammonium hydroxide), mono-, di-, and triethanolamine, sodium hydroxide, triethylamine, sodium dihydrogen phosphate, ammonium phosphate, and sodium carbonate.
[0053] In some embodiments, the emulsions of this disclosure and / or prepared by the methods of this disclosure exhibit a viscosity of 12,000 centipoise (12,000 mPa⁻²) or less, as measured using a Brookfield viscometer rotor RV6 at 20 rpm. In some embodiments, the viscosity of the emulsion does not exceed 10,000 centipoise (10,000 mPa⁻²), 7,500 centipoise (75,000 mPa⁻²), 5,000 centipoise (5,000 mPa⁻²), 3,000 centipoise (3,000 mPa⁻²), or 1,000 centipoise (1,000 mPa⁻²). In some embodiments, the emulsion has a viscosity of at least 50 centipoise (500 mPa-s), at least 100 centipoise (100 mPa-s), at least 300 centipoise (300 mPa-s), or at most or at least 500 centipoise (500 mPa-s), as measured using a Brookfield viscometer rotor LV2 at 50 rpm.
[0054] In some embodiments, the emulsions prepared by the methods disclosed herein are substantially free of organic solvents. Common organic solvents include any organic solvent with a boiling point up to 150°C at atmospheric pressure. The term “substantially free” means that the emulsion may contain up to 0.1 wt%, 0.05 wt%, or 0.01 wt% of any of these solvents, or may contain none of these solvents. These percentages are based on the total weight of the acrylic polymer particles. In some embodiments, the emulsion contains less than 0.1 wt%, 0.05 wt%, or 0.01 wt% of organic solvents based on the total weight of the acrylic polymer particles. Some specific examples of organic solvents that are substantially absent in the emulsion include those with a solubility parameter of about 9 (e.g., in the range of 8.5 to 9.5), such as cyclohexane (8.59), isobutyl acetate (9.10), and hexyl acetate (9.15). In some implementations, the emulsion is substantially free of one or more of cyclohexane, n-heptane, ethyl acetate, n-butyl acetate, isobutyl acetate, and n-hexyl acetate.
[0055] During spraying, the emulsion of this disclosure and / or prepared by the methods of this disclosure provides an adhesive capable of maintaining a clamp bond within the foam cube for one minute after spraying the emulsion. The clamp bond time represents the relative rate of accumulation of treatment strength. That is, the shorter the "clamp bond" time, the faster the bond develops treatment strength. This provides a measure of the time required to form an article operable for further processing.
[0056] The method for forming a clamp bond in a foam block is described in detail in the embodiments below and is shown in Figures 1a to 1d. For the purposes of this disclosure, the ability of the adhesive to maintain a clamp bond in a foam block, which is a polyurethane block having a side dimension of 4 inches (10.2 cm) and a minimum weight of 1.45 pounds per square foot (lb. / ft).3 )(7.08 kg / m² 2 The density of the emulsion is specified. The amount of emulsion sprayed onto one side of the foam cube is 1 to 2 grams. In some embodiments, the emulsion of this disclosure provides an adhesive capable of maintaining a clamp bond within the foam cube for 45 seconds, 30 seconds, or 20 seconds. To "maintain" the clamp bond, the clamp bond remains intact for at least 24 hours without the opposing edges of the clamp bonded surfaces separating. Generally, in higher density foams, the adhesive is more difficult to maintain a clamp bond. Therefore, if the adhesive maintains a clamp bond in a relatively high density foam, it is assumed that it will maintain a clamp bond in a lower density foam.
[0057] Examples 1 to 17 below illustrate that monomer units comprising at least one alkyl acrylate, alkyl methacrylate, or combinations thereof (wherein the alkyl group has at least 8 carbon atoms), acid-functionalized monomer units, and high-T g The emulsion of acrylic polymer particles of this disclosure, comprising monomer units of monomers, chain-end groups having at least four carbon atoms and thioether groups, monomer units of at least one of C1-C6 alkyl acrylates or C1-C6 alkyl methacrylates, monomer units of optional monomers having at least one ketone or aldehyde functional group, and optional polyfunctional crosslinking monomers, can provide an adhesive that can maintain a tight bond in a foam block for 1 minute, 45 seconds, 30 seconds, or even 20 seconds after the emulsion is sprayed. In this evaluation, the emulsion of this disclosure is comparable in performance to a polychloroprene aqueous contact adhesive (trade name “FASTBOND 100” from 3M Company, St. Paul, MN). Furthermore, as reported in U.S. Patent No. 10,221,343 (Qie et al.), the emulsion of this disclosure can provide an adhesive that can maintain a tight bond in a foam block for one minute, while containing methyl methacrylate as a high-T g Some emulsions of monomeric core-shell acrylic polymer particles do not meet this limitation. Surprisingly, according to U.S. Patent No. 10,221,343 (Qie et al.), the emulsions of this disclosure can provide an adhesive that can maintain a clamped bond in a foam block within one minute, even in the absence of the ketone-polyhydrazine crosslinking as described above.
[0058] Factors affecting an emulsion's ability to maintain a tight bond within a foam block for one minute after spraying include the emulsion's pH. Generally, emulsions containing acrylic polymer particles become more stable as pH increases, and are less likely to provide an adhesive that maintains a tight bond within a foam block for, for example, one minute during spraying. However, the pH at which an emulsion is stable can depend on the specific composition of the acrylic polymer particles, the amount of emulsifier, other additives in the emulsion, and the type of spraying system used. For example, the presence of methacrylic acid monomer units or C1-C6 or C1-C4 acrylate monomer units in the acrylic polymer particles can provide an emulsion that is less stable at pH 4 to 7 than an emulsion containing acrylic polymer particles without these monomer units. As shown in Example 14, an emulsion with a pH of 5 can provide an adhesive that maintains a tight bond within a foam block for one minute after spraying. In some embodiments, the pH range of the emulsion is 3 to 5, 3 to 6, or 3 to 7. However, since the pH at which an emulsion is stable can depend on many factors, defining a pH for every case is impractical.
[0059] We have discovered that crosslinking within or between acrylic polymer particles can be used to provide an adhesive capable of maintaining a clamp bond within a foam block for up to one minute after spraying. Crosslinking can be induced by a variety of different mechanisms as described above. As shown in Example 1 below, an emulsion comprising acrylic polymer particles (containing tert-octylacrylamide and an acid-functionalized monomer) provides an adhesive capable of maintaining a clamp bond for up to 30 seconds after spraying. In some embodiments, the acrylic polymer particles comprise monomer units of acrylate or methacrylate having more than one acrylate or methacrylate group. We have discovered that when preparing the emulsions of this disclosure, a ratio of at least 1:1 of chain transfer agent to acrylate or methacrylate having more than one acrylate or methacrylate group can be used to provide an adhesive capable of maintaining a clamp bond, and ratios of at least 2:1, at least 3:1, or at least 4:1 can be useful. In which high T g In embodiments where the monomer is tert-octylacrylamide, this ratio is greater than 1:1 and in some embodiments greater than 2:1 or at least 3:1 or 4:1. As shown in exemplary embodiments A to C, when the ratio of chain transfer agent to hexanediol diacrylate crosslinker is 1.8:1, 2:1, or 1:1, the emulsion requires a 5-minute open time before it can maintain a clamped bond in a foam cube. It is believed that higher intraparticle crosslinking in these emulsions can result in lower tackiness. Exemplary embodiment D shows that when tert-butyl methacrylate is used as a high T gWhen using a 2:1 ratio of chain transfer agent to hexanediol diacrylate crosslinking agent in the monomeric acrylic polymer particles, the emulsion fails to maintain a tight bond within the foam cube within one minute of spraying. However, when the formulation is identical except for a 1:1 ratio of chain transfer agent to hexanediol diacrylate, the emulsion of Example 7 provides an adhesive that maintains a tight bond within 20 seconds. In some embodiments, when high T... g When the monomer is tert-butyl methacrylate, the ratio of the chain transfer agent to the acrylate or methacrylate having more than one acrylate or methacrylate group does not exceed 2:1 and can be 1:1. It is difficult for those skilled in the art to analyze crosslinked polymer particles to determine the ratio of chain transfer agent to crosslinking monomer in the emulsion used to prepare the acrylic polymer particles, especially in embodiments where crosslinking also exists between particles. Therefore, the clamping adhesion evaluation clearly described herein can be used to assess whether there are appropriate amounts of chain transfer agent and crosslinking agent in the acrylic polymer particles to provide an adhesive. The composition of the acrylic polymer particles cannot be more precisely defined without unduly limiting its scope.
[0060] We have found that when the amount of chain transfer agent is too high (e.g., 0.2% by weight as in WO2020 / 245690 (published May 21, 2020)), the emulsion in the absence of a solvent may not provide an adhesive capable of maintaining a tight bond within the foam block within one minute of spraying, even when the acrylic polymer particles are crosslinked via the ketone-polyhydrazine reaction as described above. However, since we have found that the specific amount of chain transfer agent that can be used to prepare acrylic polymer particles depends on the specific monomer units in the acrylic polymer particles, it is impractical to list the exact amounts of chain transfer agents that can be used to prepare the emulsions of this disclosure.
[0061] In some embodiments, the emulsions of this disclosure provide an adhesive that maintains a clamping bond within a foam block for up to one minute after application, even after exposure to high temperature and high humidity conditions, which can be used in some applications. As shown in Examples 3 to 10 and 12 to 16, emulsions of this disclosure comprising crosslinking within acrylic polymer particles using any of the mechanisms described above and between acrylic polymer particles using a ketone-polyhydrazine reaction can provide a foam bond that withstands temperatures up to 90°C for up to 48 hours and high temperatures and relative humidity of 85%-90% for up to 200 hours. Furthermore, as demonstrated by a comparison of Examples 8 and 12, according to Exemplary Example D, when the emulsion provides an adhesive that maintains a clamping bond as described herein even in the absence of ketone-polyhydrazine crosslinking, the addition of a polyhydrazine crosslinking agent to such an emulsion can result in unexpectedly high high temperature and high humidity stability of the resulting adhesive.
[0062] In some embodiments of the emulsions and / or methods of preparing or using the emulsion or adhesive compositions of this disclosure, the emulsion or adhesive composition is substantially free of thermoplastic microspheres containing a foaming agent, such as those from Akzo Nobel under the trade name “EXPANCEL”. “Substantially free” of thermoplastic microspheres containing a foaming agent means less than 0.1 wt% or at most 0.099 wt%, 0.075 wt%, 0.05 wt%, 0.01 wt%, or 0.005 wt% based on the total weight of the emulsion. The microspheres expand when the temperature increases and are said to cause the polymer aqueous dispersion to coagulate as described in U.S. Patent Nos. 9,624,408 (Pietsch et al.) and 10,662,263 (Schmidt et al.). Advantageously, the emulsions of this disclosure do not require the addition of thermoplastic microspheres containing a foaming agent (which comes with increased cost) or the application of heat to form a bond.
[0063] Emulsions prepared according to and / or by the methods of this disclosure typically and advantageously do not require external coagulants, such as citric acid, lactic acid, acetic acid, or zinc sulfate. Therefore, methods for preparing adhesive articles comprising a first substrate and a second substrate do not require spraying a second portion containing such a coagulant in a predetermined ratio to the emulsion of this disclosure. Thus, the emulsions and methods of this disclosure avoid the disadvantages associated with two-part systems, such as the high cost and maintenance requirements of co-spraying equipment and the complexity of monitoring the ratio of the two parts (i.e., the coagulant and the adhesive composition).
[0064] In some embodiments, the emulsion of this disclosure and / or prepared by the methods of this disclosure is encapsulated in a spray container. Any of a variety of different spray containers can be used to deliver the emulsion of this disclosure and can be used in methods for preparing adhesive articles according to this disclosure. Suitable spraying equipment includes manual spray manipulators and automatic spray manipulators. Suitable manual spray manipulators include BINKS2001SS (purchased from Binks), BINKS HVLP MACH 1 (purchased from Binks), DEVILBISS MSA-503 (purchased from DeVilbiss), GRAYCO 800N (purchased from Grayco), and HVLP GRAYCO OPTIMIZER (purchased from Grayco). Suitable automatic spraying manipulators include BINKS 61 (purchased from Binks), DEVILBISS AGX-4303 (purchased from Debaishi), GRAYCO A800N (purchased from Graco), and BINKS HVLPP MACH1 (purchased from Binks).
[0065] For spraying the emulsions of this disclosure, an air-assisted spraying system can be used. Examples of available air-assisted spraying systems include those from 3M Corporation of St. Paul, Minnesota, under the trade names “3M Accuspray ONE Spray Gun System with Standard PPS” and “3M Accuspray Paint Spray System with PPS2.0”. Therefore, the spray container used for the emulsions of this disclosure can be a disposable cup or mug and a disposable liner attached to a spray gun with an atomizing head or nozzle. Compressed air can be used, for example, at pressures in the range of 0.13 MPa to 0.21 MPa.
[0066] Airless spraying systems can also be used to spray the emulsions disclosed herein. Pressure tanks (such as 1-liter tanks with a pressure up to 225 psi (1.24 MPa), derived, for example, from Apache Stainless Steel Equipment Corporation, Beaver Dam, Wisconsin) can be connected to nylon hoses (e.g., from 3M Corporation, St. Paul, Minnesota, under the trade name “3MCylinder Adhesive Hose”). The hoses can be, for example, 8, 7, 6, 5, 4, 3, 2, or 1 meter long. High-throughput metal spray guns (e.g., available under the trade names "GunJet" and "H GunJet" from Spray Systems Co., Minnetonka, Minnesota, with brass nozzles, such as "4001 UniJet", "6501 UniJet", "9501 UniJet", "1100050 UniJet", and "800050 UniJet" from Spray Systems Co.) can be easily attached to a hose. The canister can be pressurized with dry nitrogen or any desired gas.
[0067] Aerosol cans can also be used to spray the emulsions disclosed herein. Aerosol cans are available from a variety of sources, such as BallMetalpack, Broomfield, Colorado, under the trade name “Classic Tinplate Can.” Any aerosol actuator can be used, such as Aptar, Mukwonago, Wisconsin, under the trade name “Seaquist 802-24-20 / 0890-20FS,” with a color-changing valve available from Aptar under the trade name “AR-83.” Aerosols typically include a propellant. Examples of suitable propellants include nitrogen, carbon dioxide, ethane, propane, isobutane, n-butane, dimethyl ether, 1,1-difluoroethane, trans-1,3,3,3-tetrafluoropropylene, and mixtures thereof. Typically, liquid aerosol propellants such as propane, butane, and isobutane are added to the emulsion in amounts from about 5% to about 45% by weight, based on the total weight of the composition. When gases such as nitrogen and carbon dioxide are used as propellants, the gaseous propellant is typically present in amounts of up to about 10%, 8%, 6%, 5%, or 2% by weight, based on the total weight of the composition.
[0068] This disclosure provides articles comprising a first substrate and a second substrate bonded together using compositions of this disclosure, and methods for preparing such articles. The surfaces of the first and second substrates can be any desired material. In some embodiments, at least one of the surfaces of the first substrate or the second substrate comprises at least one of a metal, glass, polymer, paper, painted surface, nonwoven or woven fabric, wood, foam, or composite material. The material of the surfaces of the first and second substrates can be found throughout the substrate, or the surface can comprise a material different from the substrate bulk. In some embodiments, the surfaces of the first and / or second substrates comprise at least one of a metal (e.g., steel, stainless steel, or aluminum), glass (e.g., which may be coated with indium tin oxide), polymer (e.g., plastic, rubber, thermoplastic elastomer, or thermosetting material), paper, painted surface, or composite material. Composite materials can be made from any two or more constituent materials with different physical or chemical properties. When components are combined to prepare composite materials, materials with properties different from those of the individual components are typically obtained. Some examples of useful composite materials include fiber-reinforced polymers (e.g., carbon fiber-reinforced epoxy resins and glass-reinforced plastics); metal matrix compositions; and ceramic matrix composite materials. The surface of at least one of the first or second substrates may include polymers such as polyolefins (e.g., polypropylene, polyethylene, high-density polyethylene, polypropylene blends), polyamide 6 (PA6), acrylonitrile butadiene styrene (ABS), polycarbonate (PC), PC / ABS blends, polyvinyl chloride (PVC), polyamide (PA), polyurethane (PUR), thermoplastic elastomers (TPE), polyoxymethylene (POM), polystyrene, polyesters (e.g., polyethylene terephthalate), poly(meth)methacrylate (PMMA), and combinations thereof. The surface of at least one of the first or second substrates may also include a metallic coating on such polymers. In some embodiments, at least one of the first or second substrates comprises a transparent material, such as glass or a polymer (e.g., acrylic or polycarbonate).
[0069] In some embodiments of the adhesive article or the method of preparing the adhesive article, at least one of the first substrate or the second substrate is a foam. The emulsions of this disclosure can be used to adhere a variety of foams, including open-cell foams and closed-cell foams. The foam can be made of a variety of materials, such as polyurethanes (e.g., polyether polyurethanes and polyester polyurethanes), EPDM, acrylonitrile, PVC, polyethylene, polypropylene, polystyrene, ethylene-vinyl acetate (EVA), neoprene rubber, and styrene-butadiene rubber. The foam can have a variety of densities, including from 0.4 lb. / ft. 3 Up to 10 lb. / ft. 3 1.95 kg / m² 2 Up to 48.8 kg / m2 The range is specified. In some implementations, the foam density is 0.4 pounds per square foot (lb. / ft). 3 (Up to 5 lb. / ft.) 3 1.95 kg / m² 2 Up to 24.4 kg / m 2 The foam is an open-cell polyurethane foam within the range of 1 pound per square foot (lb. / ft). In some embodiments, the foam has a density of 1 pound per square foot (lb. / ft). 3 Up to 10 lb. / ft. 3 4.88 kg / m² 2 Up to 48.8 kg / m 2 Polyethylene closed-cell foam within the specified range. The foam can be used in a variety of products, including furniture and furniture upholstery, insulation and soundproofing, and protective packaging.
[0070] In some embodiments, at least one of the first or second substrates is a fabric (e.g., a woven or nonwoven fabric). The term "nonwoven" refers to a material having a structure of individual fibers or spindles that are sandwiched, but not in an identifiable manner such as a knitted fabric. Examples of nonwoven webs include spunbond webs, hydroentangled webs, needle-punched webs, air-blown webs, meltblown webs, and bonded carded webs. Useful nonwovens can be made from natural fibers (e.g., wood fibers or cotton fibers), synthetic fibers (e.g., thermoplastic fibers), or combinations of natural and synthetic fibers. Examples of suitable materials for forming thermoplastic fibers include polyolefins (e.g., polyethylene, polypropylene, polybutene, ethylene copolymers, propylene copolymers, butene copolymers, and copolymers and blends of these polymers), polyesters, and polyamides. The fiber can also be a multicomponent fiber, for example, having a core of one thermoplastic material and an outer sheath of another thermoplastic material. Examples of woven fabrics include twill and canvas.
[0071] In some embodiments, at least one of the first or second substrates is a low surface energy substrate. The term "low surface energy substrate" refers to substrates having a surface energy of less than 34 dynes / cm. Such materials include polypropylene, polyethylene [e.g., high-density polyethylene (HDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE)], and blends of polypropylene (e.g., PP / EPDM, TPO). In some embodiments, at least one of the first or second substrates is a medium surface energy substrate. The term "medium surface energy substrate" refers to substrates having a surface energy in the range of 34 dynes / cm to 70 dynes / cm, typically 34 dynes / cm to 60 dynes / cm, and more typically 34 dynes / cm to 50 dynes / cm. These materials include polyamide 6 (PA6), acrylonitrile butadiene styrene (ABS), polycarbonate (PC) / ABS blends, PC, PVC, polyamide (PA), polyurethane (PUR), thermoplastic elastomers (TPE), polyoxymethylene (POM), polystyrene, and poly(methyl methacrylate) (PMMA). Surface energy is typically determined by contact angle measurements, for example, as described in ASTM D7490-08.
[0072] The emulsions disclosed herein and / or manufactured by the methods of this disclosure can be used in a variety of applications. For example, the emulsion can be used to bond geotextiles. Geotextiles are typically made of nonwoven or woven fabrics and can be made of low surface energy materials such as polyolefins. Examples of materials that can be used as geotextiles include polypropylene and polyethylene terephthalate (PET). The emulsion can also be used for graphic attachment (e.g., branding or infographics) and plastic assembly. Examples of substrate surfaces that can be used for graphic attachment include polypropylene, ABS, PC, aluminum, steel, and painted surfaces. Graphic films can be made of, for example, PUR or PVC. The emulsions of this disclosure can also be used to bond dissimilar materials together. In some of these embodiments, the first substrate comprises a metal, and the second substrate comprises rubber or plastic. In some embodiments, the first and second substrates are dissimilar plastics. The emulsions of this disclosure can also be used in packaging where the first or second substrate is a cellulosic material, such as paper (e.g., polymer-coated paper), cardboard, hardwood, cork, oriented strand board, plywood, cardboard, pressed fiberboard, veneer, particleboard, wood chip laminate, and fiberboard. The wood substrate can be treated or untreated and can include birch, pine, oak, maple, mahogany, and cherry. The wood substrate can also include combinations of wood with another material, such as wood / resin composites (e.g., phenolic composites), composites of wood fibers and thermoplastic polymers, and wood composites reinforced with cement, fiber, or plastic coatings.
[0073] Some implementation schemes disclosed herein
[0074] In a first embodiment, this disclosure provides an emulsion comprising: water; an emulsifier; and acrylic polymer particles dispersed in water, wherein the acrylic polymer particles comprise at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, wherein the alkyl group has at least eight carbon atoms; at least 1% by weight of acid-functionalized monomer units based on the total weight of the acrylic polymer particles; and high T g The monomer unit includes at least one of tert-octylacrylamide, tert-butyl methacrylate, tert-butyl acrylate, isobornyl acrylate, or isobornyl methacrylate; and a chain-end group having at least four carbon atoms and attached to the polymer via a thioether group. In a second embodiment, an emulsion comprises: water; an emulsifier; and acrylic polymer particles dispersed in water, wherein the acrylic polymer particles comprise at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, wherein the alkyl group has at least eight carbon atoms; at least 1% by weight of an acid-functionalized monomer unit based on the total weight of the acrylic polymer particles; and high T gThe monomer unit comprises at least one of tert-octylacrylamide, tert-butyl methacrylate, tert-butyl acrylate, isobornyl acrylate, or isobornyl methacrylate; and a chain end group having at least four carbon atoms and connected to the polymer via a thioether group, wherein the emulsion provides an adhesive capable of maintaining a clamped bond within a foam block for one minute after spraying the emulsion. In a third embodiment, this disclosure provides an emulsion according to a first or second embodiment, wherein the acrylic polymer particles further comprise at least one monomer unit of a C1-C6 alkyl acrylate. In a fourth embodiment, this disclosure provides an emulsion according to a third embodiment, wherein the acrylic polymer particles further comprise a methyl acrylate or butyl acrylate monomer unit. In a fifth embodiment, this disclosure provides an emulsion according to any one of the first to fourth embodiments, wherein the chain end groups are present in an amount of 0.01 wt% to 0.1 wt%, 0.05 wt% to 0.1 wt%, 0.02 wt% to 0.075 wt%, 0.025 wt% to 0.06 wt%, or 0.03 wt% to 0.04 wt% based on the total weight of the acrylic polymer particles (i.e., monomer units and chain end groups). In a sixth embodiment, this disclosure provides an emulsion according to any one of the first to fifth embodiments, wherein the acrylic polymer particles constitute at least 99% of the polymer in the emulsion. In a seventh embodiment, this disclosure provides an emulsion according to any one of the first to sixth embodiments, wherein the acrylic polymer particles are crosslinked. In an eighth embodiment, this disclosure provides an emulsion according to any one of the first to seventh embodiments, wherein the emulsion has a gel content of at least 28%. In a ninth embodiment, this disclosure provides an emulsion according to any one of the first to eighth embodiments, wherein the acrylic polymer particles further comprise monomer units having at least one ketone or aldehyde functional group or at least one ketone functional group. In a tenth embodiment, this disclosure provides an emulsion according to the ninth embodiment, further comprising a polyhydrazide crosslinking agent. In an eleventh embodiment, this disclosure provides an emulsion according to any one of the first to tenth embodiments, wherein the acrylic polymer further comprises an acrylate or methacrylate monomer unit having more than one acrylate or methacrylate group. In a twelfth embodiment, this disclosure provides an emulsion according to any one of the first to eleventh embodiments, wherein the acid-functional monomer unit comprises an acrylic monomer unit, a methacrylate monomer unit, or a combination of an acrylic monomer unit and a methacrylate monomer unit. In a thirteenth embodiment, this disclosure provides an emulsion according to any one of the first to twelfth embodiments, wherein the emulsion has a pH not exceeding 7 or in the range of 3 to 7, 3 to 6, or 3 to 5.
[0075] In a fourteenth embodiment, this disclosure provides an emulsion according to any one of the first to thirteenth embodiments, further comprising a propellant. In a fifteenth embodiment, this disclosure provides an emulsion according to any one of the first to fourteenth embodiments, wherein the composition or spray adhesive composition is substantially free of thermoplastic microspheres containing a foaming agent. In a sixteenth embodiment, this disclosure provides an emulsion according to any one of the first to fifteenth embodiments, which is encapsulated in a spray container. In a seventeenth embodiment, this disclosure provides an emulsion according to any one of the first to sixteenth embodiments, wherein the alkyl group has 8 to 20, 8 to 16, 8 to 12, 8 to 10, or 8 carbon atoms. In an eighteenth embodiment, this disclosure provides an emulsion according to any one of the first to seventeenth embodiments, wherein the acrylic polymer particles have a size in the range of 50 nanometers to 10 micrometers, 50 nanometers to 5 micrometers, or 200 nanometers to 500 nanometers. In a nineteenth embodiment, this disclosure provides an emulsion according to any one of the first to eighteenth embodiments, wherein the emulsion comprises less than 0.1% by weight of an organic solvent based on the total weight of the acrylic polymer particles. In a twentieth embodiment, this disclosure provides an emulsion according to any one of the first to nineteenth embodiments, wherein the acrylic polymer particles are not core-shell polymer particles having different monomer units in the core and in the shell.
[0076] In a twenty-first embodiment, this disclosure provides an emulsion according to any one of the first to twentieth embodiments, wherein the acrylic polymer particles comprise at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combination thereof, ranging from 40% to 90% by weight, wherein the alkyl group has at least eight carbon atoms; C1-C6 alkyl acrylate ranging from 0% to 25% by weight; acid-functionalized monomer units ranging from 2% to 5% by weight; tert-octylacrylamide ranging from 3% to 15% by weight; monomer units having at least one ketone or aldehyde functional group ranging from 0% to 5% by weight, and chain-end groups ranging from 0.02% to 0.075% by weight, based on the total weight of the monomer units in the acrylic polymer particles. In some of these embodiments, the acrylic polymer particles comprise 1.6% to 2.5% by weight of an emulsifier, based on the total weight of the monomer units in the acrylic polymer particles.
[0077] In a twenty-second embodiment, this disclosure provides an emulsion according to any one of the first to twentieth embodiments, wherein the acrylic polymer particles comprise at least one monomer unit of at least one alkyl acrylate, alkyl methacrylate, or combination thereof, ranging from 40% to 90% by weight, wherein the alkyl group has at least eight carbon atoms; C1-C6 alkyl acrylate ranging from 0% to 25% by weight; acid-functional monomer units ranging from 2% to 5% by weight; tert-butyl methacrylate ranging from 10% to 30% by weight; monomer units having at least one ketone or aldehyde functional group ranging from 0% to 5% by weight, based on the total weight of the monomer units in the acrylic polymer particles; and chain-end groups ranging from 0.02% to 0.075% by weight.
[0078] In a twenty-third embodiment, this disclosure provides a method for preparing an emulsion according to any one of the first to twenty-two embodiments, the method comprising: combining a component comprising: water; an emulsifier; at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, wherein the alkyl group has at least eight carbon atoms; at least 1% by weight of an acid-functionalized monomer based on the total weight of the monomers; and a high-T g The monomer includes at least one of tert-octylacrylamide, tert-butyl methacrylate, tert-butyl acrylate, isobornyl acrylate, or isobornyl methacrylate; a chain transfer agent comprising a thiol group and at least four carbon atoms; and a polymerization initiator; and a monomer for making the at least one alkyl acrylate, alkyl methacrylate, or combination thereof; the acid-functionalized monomer, high T g Monomers, chain transfer agents, and optional emulsifiers are reacted to provide an emulsion. In a twenty-fourth embodiment, this disclosure provides a method according to a twenty-third embodiment, wherein the at least one alkyl acrylate, alkyl methacrylate, or combination thereof, acid-functionalized monomer, high-T g The monomer, chain transfer agent, and optional emulsifier are reacted to provide an emulsion at a temperature not exceeding 70°C. In a twenty-fifth embodiment, this disclosure provides a method according to a twenty-third or twenty-fourth embodiment, wherein the component further comprises an acrylate or methacrylate having more than one acrylate or methacrylate group, and wherein the ratio of the chain transfer agent to the acrylate or methacrylate having more than one acrylate or methacrylate group is at least 1:1. In a twenty-sixth embodiment, this disclosure provides a method according to a twenty-fifth embodiment, wherein the high-T... g The monomer is tert-octylacrylamide, and the ratio of the chain transfer agent to an acrylate or methacrylate having more than one acrylate or methacrylate group is at least 4:1. In the twenty-seventh embodiment, this disclosure provides a method according to the twenty-fifth embodiment, wherein the high-T gThe monomer is tert-butyl methacrylate, and the ratio of the chain transfer agent to an acrylate or methacrylate having more than one acrylate or methacrylate group does not exceed 2:1. In a twenty-eighth embodiment, this disclosure provides a method according to any one of embodiments twenty-three to twenty-seven, wherein the component further comprises a monomer having at least one ketone or aldehyde functional group, and wherein the method further comprises adding a polyhydrazine crosslinking agent to an emulsion of acrylic polymer particles. In a twenty-ninth embodiment, this disclosure provides a method according to any one of embodiments twenty-three to twenty-eight, wherein the component comprises less than 5% by weight of at least one alkyl acrylate, alkyl methacrylate, or combination thereof, an acid-functionalized monomer, a high-T g A pre-emulsion reaction of monomers and chain transfer agents is performed to form a seed emulsion, followed by the addition of the remaining amount of at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, an acid-functionalized monomer, and a high-T... g The monomer and chain transfer agent are reacted. In a thirtieth embodiment, this disclosure provides a method according to any one of embodiments twenty-four to twenty-nine, wherein the monomer comprises at least one alkyl acrylate, alkyl methacrylate or a combination thereof, an acid-functionalized monomer, and a high-T... g A pre-emulsion of at least one of the monomers or chain transfer agents is reacted in the presence of at least 5% by weight of emulsifier based on the total weight of the emulsion to form a seed emulsion, followed by the addition of the remaining amount of at least one alkyl acrylate, alkyl methacrylate, or a combination thereof, an acid-functionalized monomer, or a high-T... g The monomer and chain transfer agent are reacted in the presence of less than 5% by weight of emulsifier based on the total weight of the emulsion. In a thirty-first embodiment, this disclosure provides a method according to any one of embodiments twenty-third to thirtieth, wherein the particles have a size in the range of 50 nanometers to 10 micrometers, 50 nanometers to 5 micrometers, 100 nanometers to 300 nanometers, or 50 nanometers to 150 nanometers. In a thirty-second embodiment, this disclosure provides a method according to any one of embodiments twenty-third to thirty-first, further comprising adding an alkali to a pH not exceeding 7, in the range of 3 to 6, or in the range of 3 to 5.
[0079] In a thirty-third embodiment, this disclosure provides a method for manufacturing an adhesive article comprising a first substrate and a second substrate, the method comprising spraying an emulsion according to any one of the first to twenty-second embodiments onto at least one of the first substrate or the second substrate to form an adhesive; and adhering the first substrate and the second substrate together. In a thirty-fourth embodiment, this disclosure provides the method according to the thirty-third embodiment, wherein adhering the first substrate and the second substrate together is performed within one minute after spraying. In a thirty-fifth embodiment, this disclosure provides the method according to the thirty-third or thirty-fourth embodiment, wherein the adhesive is tacky within one minute after spraying. In a thirty-sixth embodiment, this disclosure provides the method according to any one of the thirty-third to thirty-fifth embodiments, wherein at least one of the first substrate or the second substrate is a fabric or foam.
[0080] To provide a more complete understanding of this disclosure, the following embodiments are provided. It should be understood that these embodiments are for illustrative purposes only and should not be construed as limiting this disclosure in any way.
[0081] Example
[0082] This disclosure is not limited to the embodiments described above, but is subject to the limitations set forth in the following claims and any equivalents thereof. This disclosure may be implemented in any manner appropriate to the absence of any element not specifically disclosed herein.
[0083] Unless otherwise stated, all parts, percentages, ratios, etc., in the examples and the remainder of this specification are by weight. Unless otherwise specified, all other reagents are derived from or purchased from fine chemical suppliers such as Sigma-Aldrich Company, St. Louis, Missouri, USA, or can be synthesized by known methods. The following abbreviations are used in this section: min = minute, s = second, h = hour, g = gram, kg = kilogram, lb = pound, ft = foot, cm = centimeter, ℃ = degree Celsius, oz = ounce, kPa = pascal, rpm = revolutions per minute, m 3 = cubic meter, in. = inch, mL = milliliter, L = liter, RH = relative humidity, RT = room temperature (i.e., 22°C to 23°C).
[0084] Table 1. Materials
[0085]
[0086] Test methods
[0087] Gel content percentage test
[0088] Using a moisture balance, balance the glass mat and add approximately 0.9 g of latex. Dry the material and record the solids. Then wrap the glass mat in a metal sieve and weigh it. Next, place the sample in a 4 oz (120 mL) wide-mouth bottle containing 50 mL of ethyl acetate and shake for 24 hours. Then remove the mesh-wrapped sample and dry it at 105 °C for 1 hour, then weigh it again. The mass difference is used to calculate the gel percentage. The test is repeated twice.
[0089] 90-degree foam bonding and foam bonding stability evaluation
[0090] A sample of a high-load-bearing 4-inch (10.2 cm) polyurethane foam block, part number 261401-2-S / C 4x4x4 3850GY (45 ILD), was obtained from Foam Fabricators of Minnesota, Maple Lake, Minnesota. The sample was used as the substrate, and 1-inch × 1-inch × 4-inch (2.54 cm × 2.54 cm × 10.2 cm) strips were used as the adhesive. The foam has a strength of 1.4 to 1.6 lb / ft. 3 The density is 22.4 to 25.6 kg / m³. 3 (ASTM D-3574-17) and indentation load deflection of 54 to 66 lb / 50 square inches at 25% deflection (according to ASTM D-3574-17). Lay the foam block sample flat to provide a top surface of a block with two pairs of parallel opposite sides. Spray the top surface at room temperature with 1 g to 1.5 g of the emulsion example or exemplary embodiment described below. Spray the top surface using an air-assisted spraying system (available under the trade names “3M Accuspray ONE Spray Gun System with Standard PPS” and / or “3M Accuspray Paint Spray System with PPS2.0” from 3M Corporation of Linstrom, Minnesota). The emulsion is fed through a gun with a gravity feed cup on the back and a disposable 1.8 mm plastic nozzle. After a period of time open at room temperature (i.e., the time between spraying and adhesive formation), manually apply a strip of foam to the adhesive-coated foam block surface for 5 to 10 seconds. The minimum open time required for the foam strip to adhere to the surface of the foam block at room temperature for 24 hours after the finger pressure is removed is recorded in the 90° foam evaluation under “Time” in Table 6 below.
[0091] Bond stability was then evaluated under various conditions: Condition A at 70°C for 48 hours; Condition B at 90°C for 48 hours; and Condition D at 85°C, 85% RH, for 200 hours. If no bond separation occurred during the duration of the test conditions, the result was described as "P" in Table 6 below. If the foam strip began to rise or separate from the foam block during the evaluation period, the result was described as "F" in Table 6 below. Conditions A, B, and D were achieved by placing the samples in a standard laboratory oven set to the desired conditions.
[0092] Clamp bonding and clamp bonding stability evaluation
[0093] A sample of a high-load-bearing 4-inch (10.2 cm) polyurethane foam block, part number 261401-2-S / C 4x4x4 3850 GY (45 ILD), obtained from Foam Fabricators of Minnesota, was used for high-density foam clamping bond evaluation. A sample of a lower-load-bearing 4-inch (10.2 cm) polyurethane foam block, part number 261401-1-S / C 4x4x4 2450 GY (36 ILD), also obtained from Foam Fabricators of Minnesota, was used as the substrate for low-density clamping bond evaluation. This foam has a strength of 0.85 to 1.1 lb / ft. 3 The density is 13.6 to 17.6 kg / m³. 3 (ASTM D-3574-17) and indentation load deflection of 22 to 32 lb / 50 square inches at 25% deflection (according to ASTM D-3574-17). The foam block sample is laid flat to provide a top surface of the block with two pairs of parallel opposing edges, as shown in Figure 1a. Using the same air-assisted spraying system described above for evaluating 90-degree foam adhesion, the top surface is sprayed at room temperature with 1 g to 2 g of the emulsion example or exemplary embodiment described. After a period of open time at room temperature (i.e., the time between spraying and the formation of clamp bond), the edge of a 6-inch (15.24 cm) depressor is pushed into the center of the block, and then the pair of opposing edges are aligned so that the central portion of the top surface is pushed inward toward the center of the block, as shown in Figure 1b. As shown in Figure 1c, the coated surfaces on the depressor are pinched together by hand for a few seconds from one end of the block to the other. Figure 1d shows the clamp bond retention after the finger pressure is released. After removing finger pressure, the minimum open time required to keep the clamp bond together for 24 hours at room temperature is recorded in the Clamp Bond Evaluation in Table 6 below, under “Time”. Repeat this step until the bond remains together after releasing hand pressure.
[0094] Clamp bond stability was evaluated by testing for bond separation under various conditions. Bond separation was then evaluated under the following conditions: Condition Aa, 70°C for 24 hours; Condition B, 90°C for 48 hours; Condition C, 65°C / 80-90%RH for 24 to 200 hours; and Condition D, 85°C, 85%RH for 200 hours. If no bond separation occurred within the duration of the test conditions, the result was described as “P” in Table 6 below. If the clamp bond was partially or completely opened, the result was described as “F” in Table 6 below. The time to clamp bond failure under Condition C is recorded in Table 6 below. Conditions Aa, B, C, and D were achieved by placing the samples in a standard laboratory oven set to the desired conditions.
[0095] Examples 1 to 6 and Exemplary Examples A to C
[0096] The components used to prepare Examples 1 to 6 (EX1 to EX6) and Exemplary Examples A to C (IEA to IEC) are provided in grams (g) in Table 2. Components N, O, and M (for EX3 to EX5) were mixed and added to a first 2L glass reactor equipped with a double-layer stacked flat-blade agitator. Each stack had four blades. The two sets of four blades, approximately 2 × 3.5 cm apart, were spaced approximately 6 cm apart. Components G to L and M2 (if present) were mixed together and slowly added to the first 2L glass reactor with stirring, and the resulting pre-emulsion was stirred at 600 rpm for approximately 30 minutes while being deoxygenated with nitrogen. Component A was added to a second 2L glass reactor (Ace glass 6423-20) and stirred at 130 rpm with a double-blade agitator while being degassed with nitrogen for approximately 30 minutes. The second 2L glass reactor was then heated to 30°C using two 250W IR lamps controlled by a J-KEM Apollo Two controller, and the pre-emulsion was added as component E. After a brief mixing (approximately 2 minutes), add component BD sequentially. Mix the mixture at 30°C and 130 rpm for 20 minutes, observing mild exothermic reactions (up to 32°C). After 20 minutes, heat the reaction to 55°C. Once the reaction reaches 55°C, add the pre-emulsion as component F over 4 hours. After approximately 1 hour of feeding, increase the stirring to 150 rpm. Maintain stirring of the pre-emulsion during feeding, reducing stirring as needed to ensure minimal foaming (from 600 RPM to 100 RPM at the end of feeding). After the emulsion feeding is complete, heat the reaction to 70°C, increase stirring to 200 rpm, and allow the reaction to solidify for 3 hours, then cool the reaction to room temperature. For EX3 to EX6, combine the metered loads P and Q and agitate to dissolve. If necessary, gently heat the mixture with a hot air gun until homogeneous. Then add the mixture to a 2L glass reactor while mixing. Stir the mixture for 10 minutes, then filter through coarse cotton cloth. The pH of emulsions from EX1 to EX6 and from IEA to IEC is approximately 3.8.
[0097] Table 2. Examples 1 to 6 (EX1 to EX6) and Examples A to C (IEA to IEC)
[0098]
[0099] a Add as a 10% solution in OAIB. b Obtained from Sigma-Aldrich.
[0100] The gel content of Examples 1 to 6 and Exemplary Examples A to C were evaluated using the methods provided above. The results are shown in Table 3 below.
[0101] Table 3. Gel percentage from EX1 to EX6 and from IEA to IEC
[0102] EX1 EX2 IEA IEB IEC EX3 EX4 EX5 <![CDATA[EX6 a ]]> 25.39% 26.62% 25.30% 33.57% 62.46% 68.15% 86.26% 91.78% 93.03% 27.68% 30.76% 25.29% 28.60% 65.71% 66.73% 87.02% 91.60% 90.72%
[0103] a The source of AAEM is an evaluation of Chempoint's operation.
[0104] Examples 7 to 15 and Exemplary Example D
[0105] The components used to prepare Examples 7 to 15 (EX7 to EX15) and Exemplary Example D (IED) are provided in grams in Table 4. First, a monomer mixture (AH) was prepared using the listed components. Then, a pre-emulsion (U-AA) was prepared by loading the listed surfactant, water, and a portion of the monomers into a nitrogen-purged mixing tank. Next, the seed-preparing component (IO), excluding the initiator, was loaded into a glass reactor and purged with nitrogen at room temperature for approximately 30 minutes. For Examples 7 to 12, 14, and 15, the temperature was raised to approximately 45°C, and for Example 13, the temperature was raised to approximately 60°C, and the initiator for seed preparation (P mixed with Q, followed by R or S mixed with T) was added sequentially to perform seed polymerization (approximately 20 minutes). The temperature was then raised to approximately 75°C, and the pre-emulsion (U-AA) and initiator feed (AB in AC) were started simultaneously. The initiator feed took approximately 4 hours; the pre-emulsion feed took approximately 3.5 hours. After the pre-emulsion is fed, it is cured at 75°C for approximately 1 hour, then cooled to approximately 60°C. Then, over 1 hour or 30 minutes, the chilled beverage ingredients (a solution of 0.79 g of 70% t-BuOOH in 4.71 g of water and a solution of 0.55 g of T1651 in 4.95 g of water) are fed into the reaction vessel. The emulsion is then cooled to room temperature and filtered through coarse cotton cloth.
[0106] For Examples 7 to 10 and 12 to 15, a 10% ADH aqueous solution was prepared. Approximately 100 g of the emulsion was placed in a glass or plastic container, and 1.5 g of the 10% ADH aqueous solution was slowly added to the emulsion while mixing with a pipette. For Example 14, after the addition of ADH, the pH of the emulsion was adjusted to approximately 4.5 to 5 by adding ammonia. The pH of the emulsions for EX7 to EX13, EX15, and IED was approximately 3.5 to 4.
[0107] Table 4: Examples 7 to 15 (EX7 to EX15) and Exemplary Example D (IED). Quantities are in grams (g). .
[0108]
[0109] a Add as a 20% solution in EHA
[0110] Examples 16 and 17 (EX16 and EX17)
[0111] The components used to prepare Examples 16 and 17 are provided in grams in Table 5. First, a monomer mixture (AE) was prepared using the listed components. Then, a pre-emulsion (OT) was prepared using the listed surfactant, water, and a portion of the monomers by loading them into a nitrogen-purged mixing tank. Next, 230.42 g of deionized water, 0.59 g of DSP, 19.79 g of the AE monomer mixture, 3.30 g of FES32, and 9.91 g of TO8 (diluted to 10% by weight with water) were loaded into a glass reactor and purged with nitrogen at room temperature for approximately 30 minutes. The temperature was then raised to approximately 45°C, and initiators for seed preparation (a solution of 0.32 g of KPS in 3.00 g of water and a solution of 0.06 g of T1651 in 1.00 g of water) were added sequentially for seed polymerization (approximately 20 minutes). The temperature was then raised to approximately 75°C, and the pre-emulsion (OT) and initiator feed (a solution of 0.48 g of KPS in 56.61 g of water) were simultaneously started. The initiator feed time is approximately 4 hours; the pre-emulsion feed (OT) time is approximately 3.5 hours. After the pre-emulsion feed, the emulsion is cured at 75°C for approximately 1 hour, then cooled to approximately 60°C. Then, the chilled beverage ingredients (a solution of 0.65 g of 70% t-BuOOH in 3.89 g of water and a solution of 0.38 g of T1651 in 3.44 g of water) are fed into the reaction vessel over 1 hour or 30 minutes. The emulsion is then cooled to room temperature and filtered through coarse cotton cloth. The pH of the EX16 and EX17 emulsions is approximately 3.5 to 4.
[0112] Table 5: Examples 16 and 17 (EX16 to EX17)
[0113]
[0114] Table 6: Results of 90-degree foam evaluation and clamping adhesion evaluation, including EX1 to EX17 and exemplary embodiments IEA to IAD stability test
[0115]
[0116] a Water-based contact adhesive, marketed under the trade name "FASTBOND 100" by 3M Inc. of St. Paul, Minnesota. b nt = Untested. c The source of AAEM is an evaluation of Chempoint's operation. d Clamp bond forms after a 20-second open time, but bond separation occurs at room temperature within 24 hours.
[0117] This disclosure is not limited to the above embodiments, but is subject to the limitations shown in the following claims and any equivalents thereof.
Claims
1. An emulsion comprising: water; emulsifiers; and Acrylic polymer particles dispersed in the water, wherein the acrylic polymer particles comprise monomer units of alkyl acrylate, alkyl methacrylate, or a combination thereof, wherein the alkyl group has at least eight carbon atoms; at least 1 weight percent of acid-functional monomer units based on the total weight of the acrylic polymer particles; a high T g The monomer units of the monomers include at least one of tert-octyl acrylamide, tert-butyl methacrylate, tert-butyl acrylate, isobornyl acrylate or isobornyl methacrylate; and a chain end group having at least four carbon atoms and a thioether group, The emulsion provides an adhesive capable of maintaining a pinch bond in a foam square within one minute of spraying the emulsion.
2. The emulsion according to claim 1, wherein the acrylic polymer particles further comprise at least one monomer unit of a C1-C6 alkyl acrylate.
3. An emulsion according to claim 1 or 2, wherein the acrylic polymer particles constitute at least 99% of the polymer in the emulsion.
4. The emulsion according to claim 1 or 2, wherein the acrylic polymer particles are cross-linked.
5. The emulsion according to any one of claims 1 to 4, wherein the acrylic polymer particles further comprise monomer units carrying at least one ketone or aldehyde functional group.
6. The emulsion according to claim 5, further comprising a polyhydrazide cross-linking agent.
7. The emulsion according to any one of claims 1 to 6, wherein the emulsion has a pH not exceeding 7, in the range of 3 to 6, or in the range of 3 to 5.
5.
8. The emulsion according to any one of claims 1 to 7, wherein the emulsion comprises less than 0.1 wt% of organic solvent, based on the total weight of the acrylic polymer particles.
9. The emulsion of any one of claims 1 to 8, wherein the acid-functional monomer units comprise acrylic acid monomer units, methacrylic acid monomer units, or a combination of acrylic acid monomer units and methacrylic acid monomer units.
10. The emulsion according to any one of claims 1 to 9, wherein the acrylic polymer particles are not core-shell polymer particles having different monomer units in the core and in the shell.
11. The emulsion according to any one of claims 1 to 10, wherein the acrylic polymer particles comprise in the range of 40% to 90% by weight of monomer units of at least one alkyl acrylate, alkyl methacrylate or combination thereof, wherein the alkyl group has at least 8 carbon atoms; in the range of 0% to 25% by weight of C1-C6 alkyl acrylate; in the range of 2% to 5% by weight of the acid functional monomer units; in the range of 3% to 15% by weight of tert-octylacrylamide; based on the total weight of the monomer units of the acrylic polymer particles, in the range of 0% to 5% by weight of monomer units carrying at least one ketone or aldehyde functional group, in the range of 0.02% to 0.075% by weight of the chain end groups and in the range of 1.6% to 2.5% by weight of the emulsifier.
12. A method for preparing an emulsion according to any one of claims 1 to 11, the method comprising: The method comprises: comprising water, the emulsifier, the alkyl acrylate, the alkyl methacrylate or a combination thereof, at least 1 wt % of the acid functional monomer based on the total weight of the monomers, the high T g a component combination of a monomer, a chain transfer agent containing a thiol group, and a polymerization initiator; and The alkyl acrylate, alkyl methacrylate or a combination thereof; the acid functional monomer, the high T g The monomers, the chain transfer agent, and optionally the emulsifier react to provide the emulsion.
13. The method of claim 12, wherein the components further comprise an acrylate or methacrylate having more than one acrylate or methacrylate group, and wherein the ratio of the chain transfer agent to the acrylate or methacrylate having more than one acrylate or methacrylate group is at least 1:
1.
14. The method of claim 12 or 13, wherein the components further comprise a monomer with at least one ketone or aldehyde functional group, and wherein the method further comprises adding a polyhydrazide crosslinker to the emulsion of acrylic polymer particles.
15. A method for preparing a bonded article, the bonded article comprising a first substrate and a second substrate, wherein at least one of the first substrate or the second substrate is a foam or a fabric, the method comprising: spraying the emulsion according to any one of claims 1 to 11 on at least one of the first substrate or the second substrate to form an adhesive; as well as The first substrate and the second substrate are adhered together.
Citation Information
Patent Citations
Waterborne adhesive formulations
EP2246403A1
Aqueous dispersion, its production method, adhesive and coating agent
JP2008184494A
Cross-linkable aqueous dispersion and its production method, and adhesive and coating agent
JP2008184495A
One part, fast-setting, aqueous adhesive emulsions
US10221343B2
Aqueous coagulatable polymer dispersion and use thereof as an adhesive
US10662263B2